1984
DOI: 10.1246/cl.1984.1713
|View full text |Cite
|
Sign up to set email alerts
|

FORMATION OF HELICAL SUPER STRUCTURE FROM SINGLE-WALLED BILAYERS BY AMPHIPHILES WITH OLIGO-l-GLUTAMIC ACID-HEAD GROUP

Abstract: Double-chain alkyl amphiphiles with oligo-l-glutamic acid-head group were prepared. These compounds were dispersed in water at pH 8 to 9 to form bilayer aggregates, in which helical and hollow structures were contained. New CD bands were observed in the solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(92 citation statements)
references
References 12 publications
2
89
0
1
Order By: Relevance
“…4). from four pigment gallstone patients (CSI = 88-237%) also disclosed cholesterol filaments within 1- (29)(30)(31)(32)(33)(34)(35)(36). The needlelike habit is highly suggestive of anhydrous crystallization ( 11), which might be the case because in cholesterol-rich vesicles, the 3-3 hydroxyl group of cholesterol and the sn-2 carbonyl of lecithin can be hydrogen bonded (37,38).…”
Section: Resultsmentioning
confidence: 99%
“…4). from four pigment gallstone patients (CSI = 88-237%) also disclosed cholesterol filaments within 1- (29)(30)(31)(32)(33)(34)(35)(36). The needlelike habit is highly suggestive of anhydrous crystallization ( 11), which might be the case because in cholesterol-rich vesicles, the 3-3 hydroxyl group of cholesterol and the sn-2 carbonyl of lecithin can be hydrogen bonded (37,38).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we investigated the property of chiral assemblies formed from amphiphiles with polypeptide-head groups. It was previously reported that compounds la-ld can form micelles with structural asymmetries such as ahelical4 and {3-sheet peptide-head groups, 5 and 2 can form helical superstructures composed of single-walled bilayer membranes. 6 la: R = (CH 2 ) 4 NH 2 (m + n = 3,8, 13 and 18) lb: =CH 3 (m= I, n= 10) lc: =CH 2 C 6 H 5 (m= I, n= 12) ld: =CH 2 CH(CH 3 ) 2 (m=9, n=9) * To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…51,52 At almost the same time in 1984, three independent research groups in the USA and Japan first found the formation of lipid nanotubes on the basis of this chiral molecular self-assembly. 50,53,54 The self-assembled nanotube formation from the glucoside and glucosamide lipids described later is based on this mechanism. The second growing mechanism of self-assembled nanotubes has been reported for a limited number of examples.…”
Section: Introductionmentioning
confidence: 98%